The Effect of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Return on Equity in Oil and Gas Mining Companies Listed on the Indonesia Stock Exchange Period 2017-2021 - Nanda Fitriyana; Muhammad Fuad; Meutia Dewi (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This study aims to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER) and Total Asset Turnover on Return On Equity (ROE) in Oil and Gas Mining Companies listed on the Indonesia Stock Exchange for the 2017-2021 period . The population in this study amounted to 19 companies and a sample of 14 companies using a purposive sampling technique. Methods of data analysis in this study using multiple linear regression analysis, t test, F test and test the coefficient of determination. The results showed Y = -0.473– 0.008X1 +0.012X2 +0.547X3. The results of the study using the t test show that partially Current Ratio and Total Asset Turnover have no significant effect on Return On Equity, for the Debt to Equity Ratio variable partially have a significant effect on Return On Equity. The results of the study using the F test show that the Current Ratio (CR), Debt to Equity Ratio (DER) and Total Asset Turnover simultaneously have a significant effect on Return On Equity (ROE). For the coefficient of determination test (Adjusted R2) a value of 97.7% was obtained and the remaining 2.3% was influenced by other factors not examined in this study.